2020
DOI: 10.1093/geront/gnaa109
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Nutrition Education Programs in Congregate Dining Service Settings: A Scoping Review

Abstract: Background and Objectives Nutrition education programs implemented in congregate dining service (CDS) settings have the potential to improve healthy eating behaviors among older adult populations. However, little is understood about the types of nutrition education programs that are implemented at CDS sites and the factors that impede or promote implementation efforts. The purpose of this scoping review was to examine the characteristics of CDS nutrition education programs, barriers and suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Programs based on a behaviour change theory showed positive changes in dietary outcomes. This aligns with previous findings in the literature that showed favourable behaviour change using a theoretical framework to design health promotion programs (21,25). Furthermore, findings showed that some study teams engaged with end-users as co-researchers, either through the conducting of focus groups with end users prior the program, and/or conducting of continuous evaluation during program to identify and ensure programs met their population needs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Programs based on a behaviour change theory showed positive changes in dietary outcomes. This aligns with previous findings in the literature that showed favourable behaviour change using a theoretical framework to design health promotion programs (21,25). Furthermore, findings showed that some study teams engaged with end-users as co-researchers, either through the conducting of focus groups with end users prior the program, and/or conducting of continuous evaluation during program to identify and ensure programs met their population needs.…”
Section: Discussionsupporting
confidence: 88%
“…Engaging stakeholders and end-users in the design of programs can play a significant role in its effectiveness. Culinary nutrition education and cooking classes are more likely to succeed if they first identify participant needs and involve them in the design process (25,71), as this ensures the program is relevant and beneficial for the stakeholders (72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some states require that nutrition counseling be provided on an as-needed basis by RDNs specifically, while other states provide nutrition education on a monthly basis by non-RDN professionals who have expertise in nutritional support [ 1 , 20 ]. Although nutrition education has been found to improve outcomes for older adults and is an expectation of federally funded nutrition programs [ 21 ], in 2019, only 7.6% of HDM recipients indicated that they had a nutrition counselor who offered nutritional advice on the basis of their health conditions [ 7 ]. This alarmingly low rate of nutrition counseling provided to HDM recipients is particularly concerning for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that quality of life of the individuals in need of care can be increased through being cared at home (6). Other professional home care services can also be of great benefit for older individuals with e.g., culinary dependencya support need, when someone is not able to prepare all meals by themselves (8,9). Culinary dependency is commonly associated with malnutrition (8) which in turn may have adverse health consequences (10,11).…”
Section: Introductionmentioning
confidence: 99%